An Experimental Investigation of the Performance of a Solar Heater under Climate Conditions of South of Iraq - Mahood, Hameed; Sayer, Asaad Hameed; Merdas, Samia; ALSAYER, IBRAHIM (University of Thi-Qar Journal of Science, 2023)
In general, solar water heating system can be described as a beneficial device for heating water by the utility of incident solar radiation. In the present study, an experimental solar water heater was constructed in Misan City, south of Iraq. The constructed experimental unit is a box of glass with a width of 40 cm. To measure temperatures of the experimental unit 7 K-type thermocouples were used. Three different inclination angles were investigated. The results showed that in the month of January, temperature of the solar water heater reached around 70 °C with an inclination angle of 37°. Furthermore, it was conducted that for the investigated period (January), temperatures reached the maximum at around 14 p.m. and then there was a decrease in the temperature. Moreover, it was concluded that the height of the solar water heater has a significant influence on the temperature.